Al Julanda Family Role in Oman before Islam until the end of the Prophet Era (Journal of Misan Researches, 2024)
This Study aims at introducing one of the most important families in Oman that had a political role before and after Islam, namely Al Julanda family. This family took over the throne before Islam.This study traces their role before Islam until the end of the Prophet Era. The study follows the historical approach based on describing and analyzing historical narratives by comparing modern historians' perspectives on the study subject.The study is divided into two sections and a conclusion. In the first section the study deals with the lineage of Al Julanda family before Islam, the tribes that are attributed to it, the role of the family, their welcoming to Amro bin Al Aas, and the Prophet message to Al Julanda.The study finds number of results, most notably that Al Julanda family is attributed to Me'wala bin Shams and not to Al Julanda bin Karker (which is attributed to Malik bin Fahm).The two families share the nineth grandfather. The study also proves that during the Era of Al Ezz bin Me'wala bin Shams (in the fourth and fifth century), Oman expanded to include The Arabian Gulf, Bahrain and Al Yamama).